Association of maternal KIR and fetal HLA-C genes with the risk of preeclampsia in the Chinese Han population. Issue 4 (April 2015) - Long, W.; Shi, Z.; Fan, S.; Liu, L.; Lu, Y.; Guo, X.; Rong, C.; Cui, X.; Ding, H.
Abstract Introduction This study is to investigate the distribution of inhibitory and activating killer-cell immunoglobulin-like receptors (KIRs) and the combination of KIR/human leukocyte antigen (HLA)-C in women with preeclampsia in the Chinese Han population. Methods A total of 271 patients and 295 controls were enrolled in our study. The inhibitory/activating KIR and HLA-C genes were detected using the PCR-SSP (polymerase chain reaction with sequence-specific primers) method. Results Our result showed that decreased numbers of individual activating KIR genes (2DS2, 2DS3, and 2DS5) were observed in women with preeclampsia. Furthermore, the gene frequency of total activating KIRs was significantly lower in patients compared with that of the controls (P = 0.03). The frequency of the KIR2DL1 gene was increased in women with preeclampsia when a homozygous HLA-C2 allele appeared in the fetus. Conclusion The results suggest that a KIR genetic variation might influence the risk of preeclampsia. The lack of activating KIRs could possibly lower uterine natural killer (uNK) cell activation, thereby contributing to the pathogenesis of preeclampsia. Moreover, the imbalance of the inhibitory or activating signals at the maternal–fetal interface seems to play a regulatory role in the occurrence of preeclampsia.